Efeitos da ingestão crônica de frutose no desenvolvimento de alterações metabólicas em ratos normotensos e espontaneamente hipertensos - Lirio, Layla Mendonça (2016)
The growing epidemic of metabolic syndrome has been related to the increased use of fructose by individuals, increasing its use for the production of processed foods. Recently, the use of fructose as an ingredient has increased in sweetened beverages, such as sodas and juices. We thus hypothesized that fructose intake by hypertensive rats would have a worse prognosis in developing metabolic disorder and non-alcoholic fatty liver disease. Methods. Male Wistar and spontaneously hypertensive aged 6 weeks were given water or fructose (10%) for 6 weeks. Blood glucose was measured every two weeks, and insulin and glucose sensitivity test were assessed at the end of the treatment. Systolic blood pressure was measure by plethysmography. Lean mass and abdominal fat mass was collected. Liver was analyzed to determine interstitial fat deposition and fibrosis. Results. Fasting glucose increased in animals that underwent a high fructose intake, independent of blood pressure. Also, insulin resistance was observed in both groups normotensive and hypertensive rats after fructose intake. Fructose intake caused a 2.5-fold increase in triglycerides levels in both groups. The lean mass gain did not change with fructose intake. However, we found that fructose intake significantly increased abdominal fat mass deposition in normotensive rats but not in hypertensive rats. Nevertheless, chronic fructose intake only increased fat deposition and fibrosis in the liver of hypertensive rats. Conclusions. We demonstrated that, normotensive and hypertensive rats, fructose intake increased triglycerides, abdominal fat deposition, and insulin resistance. However, hypertensive rats underwent fructose intake also develop interstitial fat deposition and fibrosis in liver. 7 Thus, essential hypertension is worsens outcomes in the development of metabolic syndrome and liver disorders in hypertensive animals when compared to normotensive animals.